2006
DOI: 10.1107/s0108768106016612
|View full text |Cite
|
Sign up to set email alerts
|

Structure and phase transitions in Ca2CoSi2O7–Ca2ZnSi2O7 solid-solution crystals

Abstract: While the incommensurability in melilites is well documented, the underlying atomic configurations and the composition-dependent phase behavior are not yet clear. We have studied the transition from the incommensurate phase to the high-temperature normal phase (IC-N), and to the low-temperature commensurate phase (IC-C) of selected members of the Ca(2)Co(1 - x)Zn(x)Si(2)O(7) system using X-ray and single-crystal electron diffraction, as well as calorimetric measurements. The space group of the unmodulated norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…It follows from the misfit between the layers formed by T(1)O 4 and T(2) 2 O 7 units and the interlayer cations [10,33]. The incommensurate effect is relatively strong, as evidenced by large departure of modulation vector q for its 1/3 value expected for ideal commensurate phase, i.e.…”
Section: Lo-to Splittingmentioning
confidence: 95%
“…It follows from the misfit between the layers formed by T(1)O 4 and T(2) 2 O 7 units and the interlayer cations [10,33]. The incommensurate effect is relatively strong, as evidenced by large departure of modulation vector q for its 1/3 value expected for ideal commensurate phase, i.e.…”
Section: Lo-to Splittingmentioning
confidence: 95%
“…The origin of the observed modulation has been explained by the structural misfit between the sizes of the tetrahedral T cations with respect to the interlayer X cations and explains the different magnitudes of modulation as a function of chemistry (Bindi et al, 2006, and references therein). On decreasing temperature the incommensurately (IC) modulated structure transforms to a commensurate lock-in structure, whereas on increasing temperature it transforms to a 3d-translational structure labelled a normal (N) structure, whereby the temperatures of the transitions are dependent on the chemical composition (Bagautdinov et al, 2002;Bindi & Bonazzi, 2003Brown et al, 1994;Hagiya et al, 1993Hagiya et al, , 2001Jia et al, 2006;Mą czkaa et al, 2015;McConnell et al, 2000;Merlini et al, 2005;Seifert et al, 1987;Seifert & Rö thlisberger, 1993;Riester & Bö hm, 1997;Riester et al, 2000;Rö thlisberger et al, 1990;Schaper et al, 2001). For Ca 2 MgSi 2 O 7 and Ca 2 Al 2 SiO 7 high-pressure studies have shown a phase transition from the IC to an N tetragonal phase comparable to that observed with increasing temperature (Ardit et al, 2011(Ardit et al, , 2012Merlini et al, 2009;Yang et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The strong modulation at 4.2 K approaches the wave vector a = 0.5, which would correspond to a commensurate superstructure. Such a behavior is known from other minerals as, for example, certain melilite-type compounds where a transformation from the incommensurate high-temperature phase into a low-temperature commensurate lock-in phase has been observed (Jia et al 2006). …”
Section: Transmission Electron Microscopymentioning
confidence: 96%